Understanding leadership development within new medical schools in Africa - Wessels, Quenton Bester (Department of Health Sciences Education, 2022)
The transient and multifaceted nature of leadership in Health Professions Education has changed over time. Programme directors associated with medicine, pharmacy, nursing, allied health and those involved in a clinical setting typically serve as managers and leaders concurrently. Furthermore, managers in modern organisations are expected to fulfil leadership roles. Leader and leadership development are inter-reliant phenomena. Moreover, the growth of leaders, the mutual development within a group and the consequent development of an organisation in the context of health professions education HPE require framing. This is especially true when leaders are faced with an array of constraints in low- and middle-income countries. In order to appreciate leader development, we need to ask “what qualities do we need to develop in our leaders?” and for leadership development “what qualities do we need to develop in our organisation?”. Thus, within the context of the current study we essentially ask: “What qualities have developed in our leaders, organisation and the consortium?” The current study sought to understand leadership development of appointed and emergent leaders in new medical schools in Africa. A mixed-methods approach was employed and the data collection instruments included: a Likert scale survey, a multiple case study approach and a qualitative document analysis (QDA). A total of 29 surveys (64.5% response rate) were returned and 10 successful interviews were conducted after ethical approval and obtaining consent. Many of the participants fulfilled multiple roles as lecturer (linked to the basic medical sciences), departmental head and/or a clinical teaching position in the hospital. Their academic positions and seniority as leaders included deans, a deputy dean, a programme director, heads of departments (HODs), medical educationalists and lecturers. Any additional biographical information was excluded in the study in order to ensure anonymity of the participants. Finally, the QDA relied on a four-step Scott method and considered a total of 58 documents that ranged from meeting agendas and reports, scholarly works, book chapters, newsletters, external reports, conference proceedings, and the CONSAMS (Consortium of New Sub-Sahara African Medical Schools) constitution. Findings from the current study led to the development of a framework to navigate the complex nature of leadership development in new medical schools in Africa. The three-tier framework views leadership development of the individual, the institution and within the context of collaboration such as a consortium. Leadership development at an individual level is dependent on the interplay between an institutional climate, contextual forces and resultant responses of leaders. Five archetypes of leadership development were identified at an individual level: the leader in front, the strategist, the silenced leader, becoming a leader and the leader as manager. The archetypes are the result of biographical, programmatic, institutional and contextual forces. The leader subsequently interprets these forces in order to negotiate their roles, position and course of action. Leadership development at an institutional level occurs within a hierarchical system and can sometimes occur in isolation. Development is often hampered by day-to-day activities that are reactive in nature in a bid to negotiate the various forces. The formation of teams and coalitions are hampered by climate factors such as ineffective engagement of colleagues, poor bilateral communication, perceived misalignment of the values and unsuccessful collaboration. The formation of networks and alliances, as in the case of CONSAMS, drives the leadership development at a collaborative level. Within this context, leadership development is largely dependent on effective communication and feedback. Within a consortium, each participant contributes from the position of their dominant archetype, but are also temporarily freed from institutional constraints to think more strategically. The consortium generates a unique climate where the heterogeneity of leaders through their archetypes can be challenged, tested and strengthened. Interaction within the consortium permits freedom, more so than within the domain of an institution.